Problems and related issues of buying offices in relation to the quota phase out - Suba, Ronald L.; Escano, Maria Monica R. (2001.)
The first chapter of this study provides an overview of the quota phase-out, thr buying office, and the problems it is currently experiencing and will face in the coming future. The buying office is the distributing arm of the Philipppine Garment Export Industry and plays a key role in the continuous development by its effort to market our local products abroad. The industry being under the World Trade Organization (WTO) would need to undergo changes that would help them survive the Post-Quota era in 2005. It is therefore significant to assess and study the existing problems and issues that affect the operation of buying offices in relation to the on going quota phase-out. The preparations and coping measures undertaken by the buying office and trading companies was also considered in its objective to overcome or at least hasten the negative effects of the quota phase-out. The second chapter aims to explain some of the fundamental concepts that are relevant to the study. The chapter gave an in depth report of the global and local scenario in terms of the trade policy and the Philippine Garment Export Industry. The chapter also discussed the principle of export quota system, export quota allocation and the focal point of the study, the buying offices. The GTEB and FOBAP were also included in this chapter because they play significant roles in the operation of the buying offices. The trend in the garment export industry has become relatively unpredictable. For the past years, exports of garment export industry has become relatively unpredictable. For the past years, exports of garments and textile to the world had been decreasing at an alarming rate. Statistics and studies show, and likewise, garment exporters themselves admit, that the industry has heavily relied on the dictates of buyers at the expense of bargaining power. In a situation where there is too much supply and the demand is scarce, added value spell out the difference(Global Competitiveness in a Quota-Free Environment, PTTC August 1999). The study had fifteen respondents representing fifteen different buying offices here in Metro Manila. Thirteen were the general managers or country head of their company while two were merchandisers. The study was directed to that the top-level management who would be the most knowledgeable and credible source of information in connection with the topic at hand. The sample size was 54% of the potential and active buying offices listed in the directory of FOBAP, the industry sector's main organization. Some of the general managers interviewed were also directors and officers of the aforementioned organization. The researcher acquired the needed information and data from the sample. The first method was through personal interview with the general managers or merchandisers. The interview duration lasted 10-15 minutes guided by a prepared outline of the questions that should asked. The second part was the five-page prepared questionnaire, which was able to determine more specific data that were relevant to the study. The questionnaire, which was able to determine more specific data that were relevant to the study. The questionnaire, which was able to determine more specific data that were relevant to the study. The questionnaire after being deliberated and reviewed with the researcher's thesis adviser, has been pre-tested by one general manager. After some minor changes, the questionnaires were distributed to other purposively chosen respondents. Both methods were successful in gathering enough information to support the study. The result of the study shows a high level of awareness among buying offices with regards to the ongoing quota phase out. Most of the respondents are pessimistic of the chances of the garments industry to survive the post quota scenario. The study shows the current problems of the buying offices like the decrease in their volume of orders, low competitiveness among vendors and possible restructuring of their roles as buyer's agent. The coping measures that are being implemented by the buying office are also stated in the study together with their plan of action for the post quota scenario. The buying offices also provided insights on what changes in role they think will happen after the quotas are completely phases out by year 2005. Based on the results of the study done, the researcher concludes that buying offices are indeed experiencing problems and other issues that are affecting their operation as the distributing arm of the local garment export industry. The buying office also forecast decrease in volumes of performance or booking after quota phase out. They also think that they will no longer be able to cater more on the lower-end products because of the more stiff price competition with other countries. The employment rate on their business is also expected to decrease because of less business movement and their buyers would implement managerial changes in terms of downsizing. The trend of Information Technology will also buying offices creating a need for role redefining and organizational restructuring. There will also be important developments in the roles of buying offices in the future when the quotas are phase out. The researcher recommends the following action that need to be undertaken. Firstly, promote more inquiries and studies that will determine how to solve problems addressed by the study. Secondly, the industry should continuously coordinate with the government agencies to be able to deliberate and arrive at policies that will provide the industry assistance and protection, especially during this quota phase-out transition period. Thirdly, the industry should strive hard to improve itself and not resist the call of globalization. The researcher sees the need for a continuation of this study after the quota has been completely phase out to be able to assess the actual impact on it on the buying offices and also on the garment export industry as a whole.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Offices--Philippines--Commercial policy; Clothing trade--Philippines--Commercial policy